ILC2 Orchestration of Local Immune Function in Adipose Tissue - Bénézech, Cécile; Jackson-Jones, Lucy Helen (Frontiers in Immunology, 2019)
ILC2s were originally identified as IL-5 and IL-13 secreting ‘natural helper cells’ present within the fat associated lymphoid clusters of the mesenteries in both mouse and man. The presence of ILCs in adipose tissue has more recently expanded to include all ILC groups. Since their initial discovery, our knowledge of these cells and their role in adipose immune responses has expanded significantly. In this review we summarise the current literature on the role that ILC2s play in orchestrating adipose tissue function in both lean and obese states. We go on to address new data detailing interactions of adipose ILCs with innate like B-cells (IBC) and discuss how this interaction results in localised protection of mucosal sites during infection and inflammation via the production of innate antibodies.